Identification of EPCAM mutation: clinical use of microarray. Issue 6 (10th May 2017) - Tan, Queenie K.‐G.; Cardona, Diana M.; Rehder, Catherine W.; McDonald, Marie T.
Key Clinical Message: We report a case of an infant with congenital tufting enteropathy (CTE) who presented with severe failure to thrive despite multiple interventions. This study illustrates that CTE may be missed by endoscopy, and the use of chromosomal microarray and immunohistological analysis may be integral to diagnosis. Abstract : We report a case of an infant with congenital tufting enteropathy (CTE) who presented with severe failure to thrive despite multiple interventions. This study illustrates that CTE may be missed by endoscopy, and the use of chromosomal microarray and immunohistological analysis may be integral to diagnosis.